CD153/CD30 signaling promotes age-dependent tertiary lymphoid tissue expansion and kidney injury - Sato, Yuki; Oguchi, Akiko; Fukushima, Yuji; Masuda, Kyoko; Toriu, Naoya; Taniguchi, Keisuke; Yoshikawa, Takahisa; Cui, Xiaotong; Kondo, Makiko; Hosoi, Takeshi; Komidori, Shota; Shimizu, Yoko; et al. (The Journal of clinical investigation, 2022)
Tertiary lymphoid tissues (TLTs) facilitate local T and B cell interactions in chronically inflamed organs. However, the cells and molecular pathways that govern TLT formation are poorly defined. Here, we identified TNF superfamily CD153/CD30 signaling between 2 unique age-dependent lymphocyte subpopulations, CD153+PD-1+CD4+ senescence-associated T (SAT) cells and CD30+T-bet+ age-associated B cells (ABCs), as a driver for TLT expansion. SAT cells, which produced ABC-inducing factors IL-21 and IFN-γ, and ABCs progressively accumulated within TLTs in aged kidneys after injury. Notably, in kidney injury models, CD153 or CD30 deficiency impaired functional SAT cell induction, which resulted in reduced ABC numbers and attenuated TLT formation with improved inflammation, fibrosis, and renal function. Attenuated TLT formation after transplantation of CD153-deficient bone marrow further supported the importance of CD153 in immune cells. Clonal analysis revealed that SAT cells and ABCs in the kidneys arose from both local differentiation and recruitment from the spleen. In the synovium of aged rheumatoid arthritis patients, T peripheral helper/T follicular helper cells and ABCs also expressed CD153 and CD30, respectively. Together, our data reveal a previously unappreciated function of CD153/CD30 signaling in TLT formation and propose targeting the CD153/CD30 signaling pathway as a therapeutic target for slowing kidney disease progression.